Deficit in Adipose Differentiation in Mesenchymal Stem Cells Derived from Chronic Rhinosinusitis Nasal Polyps Compared to Nasal Mucosal Tissue - Chiarella, Emanuela (Int J Mol Sci, 2020)
Chronic rhinosinusitis of the nasal mucosa is an inflammatory disease of paranasal sinuses, which causes rhinorrhea, nasal congestion, and hyposmia, and in some cases, it can result in the development of nasal polyposis. Nasal polyps are benign lobular-shaped growths that project in the nasal cavities; they originate from inflammation in the paranasal mucous membrane and are associated with a high expression of interleukins (IL)-4, IL-5, IL-13, and IgE. Polyps derive from the epithelial–mesenchymal transition of the nasal epithelium resulting in a nasal tissue remodeling. Nasal polyps from three patients with chronic rhinosinusitis as well as control non-polyp nasal mucosa were used to isolate and cultivate mesenchymal stem cells characterized as CD73(+), CD90(+), CD105(+)/CD14(−), CD34(−), and CD45(−). Mesenchymal stem cells (MSCs) cultures were induced to differentiate toward adipocytes, where lipid droplets and adipocyte genes PPARγ2, ADIPO-Q, and FABP4 were observed in control non-polyp nasal mucosa-derived mesenchymal cells but were scarcely present in the cultures derived from the nasal polyps, where apoptosis was evident. The modulation of the response to adipogenic stimulus in polyps represents a change in the molecular response that controls the cascade required for differentiation as well as possible means to specifically target these cells, sparing the normal mucosa of the nasal sinuses.